Taxonomic notes Maranta (Marantaceae): a new combination and an updated infrageneric classification for the genus - Luna, Naédja K. M.; Fernandes, Geysla C.; Christenhusz, Maarten J. M.; Pessoa, Edlley M. (Phytotaxa, 2025)
N/A